Faktor Anteseden dan Konsekuensi Green Supply Chain Management - Rakhmawati, Antin; Rahardjo, Kusdi; Kusumawati, Andriani (Universitas Diponegoro, 2019)
Business activites besides having a fuction to improve the economy, its also have a role to influencing the environment, if the business concept doesn't consider the environment, it will causing decrease of environmental quality. therefore, the purpose of this study is to examine about the application of green supply chain management, that is the concepts with consideration of environmental aspects in all supply chains, and to the explain of factors that become antecedents in influencing the implementation of green supply chain management and its impact on performance. this research explains the relationship between variabels, That are antecedents of green supply chain management, namely strategic orientation and government regulation, and the consequence factors of green supply chain management namely environtmental performance. the object in this study is medium size entreprised of food and beverage sectors in Pasuruan Regency. This study using a cluster sampling method involving 114 respondents and using PLS, for data analysis, with SmartPLS 3.0 software analysis tools. the results of this study indicate that there is a significant positive relationship between strategic orientation and government regulation toward green supply chain management, there is a significant positive relationship between strategic orientation and government regulation towards environmental performance through green supply chain management.